Sources of plutonium isotopes and 137Cs in coastal seawaters of Liaodong Bay and Bohai Strait, China and its environmental implications. (May 2018) - Hao, Yongpei; Xu, Yihong; Pan, Shaoming; Song, Xiaowei; Zhang, Kexin; Guo, Haiting; Gu, Zhi
Abstract: In order to investigate the sources of plutonium in seawaters of Liaodong Bay and Bohai Strait, China, surface seawater samples were collected and analyzed for 239+240 Pu and 137 Cs by radiochemical separation combined with ICP-MS and γ-spectrometry, respectively. A large variation of 239+240 Pu activities was observed, ranging from 1.993 to 29.677 mBq/m 3 in the Liaodong Bay and from 0.932 to 10.183 mBq/m 3 in the Bohai Strait. 137 Cs activities showed little variation between the investigated locations, which was attributed to the different behavior characteristics of 239+240 Pu and 137 Cs in seawaters. The 240 Pu/ 239 Pu atom ratios showed a significant variation between the Liaodong Bay (0.185) and Bohai Strait (0.225), indicating that Pu derived from the Pacific Proving Grounds might have been transported to the Bohai Strait but not yet to the Liaodong Bay, which could further provide valuable reference for evaluating the seawater exchange cycle between the Bohai Sea and Yellow Sea. Graphical abstract: Highlights: 239+240 Pu activities showed a large variation in surface seawaters in the Liaodong Bay and Bohai Strait. PPG-Pu might have been transported to the Bohai Strait. The seawater exchange cycle of Bohai Sea and Yellow Sea was preliminary evaluated.